Developing a teaching guidebook of speaking for daily activities based on Flanders interaction analysis categories system (FIACS) - Nanik Mariyati; Nila Susanti; Suyik Binarkaheni; Yuslaili Ningsih (Journal of English Language Teaching and Learning (JETLE), 2026)
This research focused on developing a teaching guidebook for the Speaking for Daily Activities course based on the Flanders Interaction Analysis Categories System (FIACS). The guidebook was designed to provide practical teaching mechanisms that helped speaking lecturers monitor and reflect on classroom interactions, addressing the absence of a reliable reflection tool in guidebook form. FIACS categorized classroom interaction into three types: Teacher Talk (TT), Student Talk (ST), and silence or confusion. The research employed the ADDIE model, consisting of Analyze, Design, Develop, Implement, and Evaluate stages, to develop a FIACS-based teaching guidebook for the Speaking for Daily Activities course. The study was conducted in the English study program and involved speaking lecturers as the participants. The guidebook was designed to assist lecturers in monitoring and reflecting on classroom interaction patterns through observation sheets, coding procedures, scoring systems, and reflection guidelines. The implementation and evaluation results indicated that the guidebook functioned effectively as a structured reflection tool, although revisions were needed to provide a more detailed interaction-frequency matrix. Overall, the FIACS-based guidebook proved useful in measuring and balancing Teacher Talk (TT), Student Talk (ST), and silence in speaking classrooms.